2008
DOI: 10.1680/geng.2008.161.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Loading tests on compacted soil, bottom-ash and lime layers

Abstract: This paper addresses the interpretation of loading tests bearing on a layered system formed by a compacted soil, coal bottom-ash and carbide lime top-layer overlying a compressible residual soil stratum. Load–settlement behaviour is observed from tests carried out using circular steel plates ranging from 0.30 to 0.60 m diameter on the top of a 0.15–0.60 m thick artificially cemented layer. Field data demonstrate the effectiveness of compacted soil–ash–lime layers in increasing bearing capacity and reducing fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…2 that BRS (25z FA) mixture pH variation with lime addition (ICL method) results are very similar to the BRS pH tests. So, based on such results, 3z of lime is the minimum amount of lime chosen for all mixtures studied (BRS, BRS (12.5z FA), BRS (25z FA)), besides of 5z, 7z and 9z (such percentages were chosen considering international experience with soil-‰y ash-lime (Mitchell, 1981;Consoli et al, 2001Consoli et al, , 2008). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 that BRS (25z FA) mixture pH variation with lime addition (ICL method) results are very similar to the BRS pH tests. So, based on such results, 3z of lime is the minimum amount of lime chosen for all mixtures studied (BRS, BRS (12.5z FA), BRS (25z FA)), besides of 5z, 7z and 9z (such percentages were chosen considering international experience with soil-‰y ash-lime (Mitchell, 1981;Consoli et al, 2001Consoli et al, , 2008). …”
Section: Methodsmentioning
confidence: 99%
“…In spite of the numerous applications, there are no dosage methodologies for the assessment of a target soil-‰y ash-lime strength, based on rational criteria as in the case of soil-cement technology, where the voids/cement ratio plays a fundamental role (Consoli et al, 2007b(Consoli et al, , 2009(Consoli et al, , 2010. The need for such dosage results from the fact that soil-‰y ash-lime shows a complex behavior that is aŠected by many factors, for example the physical-chemical properties of the soil and the ‰y ash, curing time, quantity of ‰y ash, amount of lime and porosity of the mixtures (e.g., Mitchell, 1981; Transportation Research Board (TRB), 1987; Kamon and Nontananandh, 1991; Nontananandh and Kamon, 1996; Consoli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As per the proposed model, the foundation fails when bearing capacity failure occurs within the clay soil. Kenny and Andrawes (1997), Consoli et al (1998Consoli et al ( , 2008Consoli et al ( , 2009 and Ornek et al (2012b) also reported good agreement between the measured and estimated values of the bearing capacity when the reduced shear strength value of bottom weak layer was considered to calculate the bearing capacity for the two-layer soil system (strong soil over weak soil). A similar method has been used by Consoli et al (2009) and Ornek et al (2012a, 2012b.…”
Section: Evaluation Of Tensile Strength Mobilised At Reinforcementmentioning
confidence: 65%
“…This practice has been widely used, as described by Lin and Wong (1999), Andromalos et al (2001) and Hussin and Garbin (2012). The research group at Federal University of Rio Grande do Sul, Brazil (e.g., Thomé et al, 2005;Consoli et al, 2008Consoli et al, , 2009aConsoli et al, ,b,c, 2010Consoli et al, , 2011Consoli et al, , 2012Consoli et al, , 2013aConsoli et al, ,b, 2014aFestugato et al, 2013;Faro et al, 2015) has been studying key parameters dictating strength and stiffness of lime/cement treated soils.…”
Section: Introductionmentioning
confidence: 99%